Optimalisasi Kepuasan Masyarakat Desa Jatirenggo melalui Implementasi Aplikasi JALANTOL dan Peningkatan Kompetensi Perangkat Desa - Rudi Wibowo; Erna Nur Faizah; Imran Syah; Nuning Nurna Dewi; Ali Basyah (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2026)
This study aims to analyze the effect of the implementation of the JALANTOL (Jatirenggo Online Integrated Service) application and the competence of village officials on community satisfaction in Jatirenggo Village, Lamongan Regency. The background of this research problem focuses on efforts to improve the quality of public services by utilizing digital technology and the competence of village officials. The research method used is quantitative with a survey approach, where data were collected through distributing questionnaires to 95 respondents selected using a purposive sampling echnique. The collected data were analyzed using multiple linear regression. The results showed that the implementation of the JALANTOL application had a significant positive effect on community satisfaction, by increasing efficiency, fulfillment of needs, system availability, and privacy. In addition, the competence of village officials was also proven to have a significant effect on community satisfaction, where indicators such as motives, traits, self-concept, knowledge, and skills affect the quality of services received by the community. Simultaneously, these two variables have a positive effect on community satisfaction. The conclusion of this study is that the effective implementation of the JALANTOL application and increasing the competence of village officials can significantly increase community satisfaction.